Nixon's jump into the cold water - Carl Landauer (Intereconomics, 1971)
Although at first publlc reaction to President Nixon's Economic New Deal was very positive, criticism has been increasing during the last weeks. The most controversial issue at the moment in the USA Is without doubt the wage and price freeze imposed for 90 days.
Keywords: 330; USA